1968
DOI: 10.1111/j.1469-8986.1968.tb02783.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal Activity in Non‐palmer Skin Sites

Abstract: This study was undertaken to explore the human body for GSR sites, which would parallel palmar GSR activity, but would not impede the subject or be prone to artifact. Specific resistance values ranged from 10,000 to 800,000 ohm‐cm2. Specific resistance of the scalp was consistently lower than other areas. Spontaneous activity was observed at all non‐palmar, non‐plantar sites except the scalp. At times, this activity was found to be present when the palm was quiescent. Evoked non‐palmar, non‐plantar activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
4
15
0
Order By: Relevance
“…Atypical responses have been reported as being present during stage 3 sleep (Johnson & Lubin, 1966), noted by us in two sleep records, and reported by Rickles and Day (1968) as being obtained from nonpalmar sites. Atypical responses have been reported as being present during stage 3 sleep (Johnson & Lubin, 1966), noted by us in two sleep records, and reported by Rickles and Day (1968) as being obtained from nonpalmar sites.…”
Section: Nonspecific Fluctuationsmentioning
confidence: 74%
“…Atypical responses have been reported as being present during stage 3 sleep (Johnson & Lubin, 1966), noted by us in two sleep records, and reported by Rickles and Day (1968) as being obtained from nonpalmar sites. Atypical responses have been reported as being present during stage 3 sleep (Johnson & Lubin, 1966), noted by us in two sleep records, and reported by Rickles and Day (1968) as being obtained from nonpalmar sites.…”
Section: Nonspecific Fluctuationsmentioning
confidence: 74%
“…We cannot account for these differences on the basis of anatomy alone since, for example, significant gender differences were found at the LR acupoint but not at the anatomically similar, nearby SP acupoint on the foot (Figure 1). Although no other studies have looked specifically at SC at the Source (Yuan) points, Rickles and Day [23] found that EDA measurements at nearby skin sites around the ankle are similar to EDA on the plantar surface of the foot. While we did not measure acupoints on the plantar surface of the foot, there was significant variation between SC on ankle acupoints (KI3, GB40) and other foot locations, and we did not see this level of SC variation at acupoints on the hand.…”
Section: Figurementioning
confidence: 98%
“…4 Systematic investigations comparing the SCL on various body sites have revealed that the scalp possesses almost 4½ times as much conductance as the palmar sites of the fingers (Edelberg, 1967), presumably due to the numerous hair follicles. 5 However, comparisons of SRRs at corresponding sites (Rickles & Day, 1968) yielded that all nonpalmar sites, except the feet, display long periods of electrodermal inactivity, whereas at the same time spontaneous and evoked EDRs can be obtained from palmar sites. The special suitability of the palmar and plantar 4 In a recently performed study for comparison of electrode creams for electrodermal recording, Tronstad, Johnsen, Grimnes, and Martinsen (2010; see also Sect.…”
Section: Choice Of Sitesmentioning
confidence: 99%
“…Rickles and Day (1968) also Fig. 2.7 Medial side of the right foot with the recommended recording sites A and B for exosomatic recording, and position E of the inactive electrode for endosomatic recording 6 Toyokura (1999) recorded SPRs following electric stimulation of the left median nerve at the wrist from 41 participants (9 females, 32 males; aged 22-60 years) from palmar and plantar sites in parallel, using reference electrodes on the nail of the index finger and the big toe.…”
Section: Choice Of Sitesmentioning
confidence: 99%